The Bank of Canada's Monetary Policy Framework : Have Recent Changes Enhanced Central Bank Credibility? - Ito, Takatoshi (IMF Working Papers; Working Paper ;, 1997)
In recent years the Bank of Canada has made important changes in the way it conducts monetary policy. In particular, the bank has adopted explicit inflation targets and introduced significant changes to its operational framework designed to increase transparency and reduce market uncertainty. This paper examines the key issues associated with the recent changes in the Bank of Canada's monetary policy framework and analyzes various indicators of central bank credibility.